2007
DOI: 10.1007/s10633-007-9090-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and structural assessment of the central retina following intravitreal injection of bevacizumab for treatment of macular edema

Abstract: Intravitreal injection bevacizumab resulted in reduction in the central retinal thickness and mild to moderate improvement in the mfERG amplitudes in this short-term study. The visual acuity changes did not directly correlate with the reduced central retinal thickness or improvement in mfERG. The short-term results showed no serious ocular adverse effects. Therefore on short-term follow up the off label drug showed improvement of macular edema secondary to vein occlusion and diabetic retinopathy with no demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 32 publications
4
13
1
1
Order By: Relevance
“…In a previous study, we demonstrated that less extensive PRP is needed to control high-risk PDR if the combination of PRP and IVR is used [20], and there is also evidence that intravitreal anti-VEGF drugs can improve ERG responses if associated with reduction of retinal edema [26].…”
Section: Introductionmentioning
confidence: 97%
“…In a previous study, we demonstrated that less extensive PRP is needed to control high-risk PDR if the combination of PRP and IVR is used [20], and there is also evidence that intravitreal anti-VEGF drugs can improve ERG responses if associated with reduction of retinal edema [26].…”
Section: Introductionmentioning
confidence: 97%
“…It has been used to evaluate retinal function after PDT or intravitreal injection of bevacizumab for patients with AMD or with other macular diseases and has been proved to be a good measure to observe the functional changes of retina after treatment [19,32,33]. To assess objectively the influence of combined intravitreal bevacizumab and PDT on retinal function, we investigated the changes of the multifocal ERG at 1, 3 and 6 months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have only been short-term studies on the safety and efficacy of intravitreal bevacizumab including electrophysiological evaluation [6][7][8][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In three recent clinical studies, average mfERG macular responses in the fovea and parafovea showed increased P [1] amplitude after bevacizumab injections as compared to baseline recordings [18][19][20].…”
Section: Discussionmentioning
confidence: 99%